Self-assembly of Cis-configured squaraine dyes at the TiO2-dye interface: far-red active dyes for dye-sensitized solar cells - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
To synergize both steric and electronic factors in designing the dyes for dye-sensitized solar cells, a series of cis-configured unsymmetrical squaraine dyes P11-P15 with suitably functionalized alkyl groups and squaric acid units containing the electron-withdrawing groups were synthesized, respectively. These dyes capture the importance of (i) the effect and position of branched alkyl groups, (ii) mono- and di-anchoring groups containing dyes, and (iii) further appending the alkyl groups through the cyanoester vinyl unit on the central squaric acid units of DAD-based cis-configured squaraine dyes. All the above factors govern the controlled self-assembly of the dyes on the TiO2 surface which helps to broaden the absorption profile of the dyes with an increased energy-harvesting process. With respect to the position of the branched alkyl groups, dye P11 with the sp(3)-C and N-alkyl groups away from the TiO2 surface showed a better device efficiency of 5.98% (J(sc) of 14.46 mA cm(-2), V-oc of 0.576 V, and ff of 71.8%) than its positional isomer P12 with 3.45% (J(sc) of 8.78 mA cm(-2), V-oc of 0.554 V, and ff of 70.9%). However, with respect to the dyes containing mono- and di-anchoring groups, P13 with two anchoring units exhibited a superior device performance of 7.58% (J(sc) of 17.12 mA cm(-2), V-oc of 0.618 V, and ff of 71.7%) in the presence of optically transparent co-adsorbent CDCA (3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid) than dyes P11 and P12.